PEMBERDAYAAN POTENSI ADAT DAN BUDAYA DALAM MENINGKATKAN KEHIDUPAN MODERASI BERAGAMA - Siregar, Budi Gautama; Lubis, Aswadi; Hadamean, Barkah; Hasibuan, Ali Amran (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2023)
The religious moderation program is aimed at creating attitude and efforts to make religion a basis and principle to avoid radical and extreme behavior and ethnocentrism and always strive for a middle way that unites, integrates and equalizes all elements, heteregonities in the life of society, The method used is community service-based research, namely Participation Action Research (PAR), which is a service carried out as well as research with the aim of empowering the community in overcoming the problems they face and increasing their potential to lead to a better social life. The approach to empowering the Danau Bale community in Rantau Selatan District, Labuhan Batu Regency. The results found after community empowerment through interviews, FGDs and observations found the results The customary and cultural conditions of the Danau Balai community, Rantau Selatan District, have a diversity of customs and cultures based on their respective tribes, there are Javanese, Toba Batak and Mandailing Batak and Chinese customs. In daily life, only some of the customs and culture of the community are still implemented and guided in daily life.  The life of religious moderation in the Danau Balai community is going well, there is cooperation between communities in daily activities in various fields of community life, both in the social and religious fields. Empowerment of customary and cultural potential is carried out with assistance activities in the form of socialization of empowerment of customary and cultural potential to the Danau Balai Village community, these activities have a significant impact on the community, can remind the community about the diversity of customs and culture and the importance of continuing to be preserved and implemented in everyday life, where so far many people have forgotten it and are no longer implemented in everyday life.